2016
DOI: 10.1111/jpn.12547
|View full text |Cite
|
Sign up to set email alerts
|

Porcine hepatocyte–Kupffer cell co‐culture as an in vitro model for testing the efficacy of anti‐inflammatory substances

Abstract: As Kupffer cells are highly involved in the regulation of hepatic inflammatory response, the main goal of this study was to improve and to characterize a hepatocyte-Kupffer cell co-culture of pig origin for modelling endotoxin-induced hepatic inflammation and for testing the efficacy of potential anti-inflammatory substances. This monolayer co-culture was prepared from primary isolated swine hepatocytes and Kupffer cells in the ratio of 6:1 and 2:1, mimicking different states of liver inflammation. The prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Aside from its primary function as an energy source for colonocytes, it is a strong mitosis promoter and a differentiation agent for intestinal epithelial cells [8], as it acts as a histone deacetylase (HDAC) inhibitor [9]. It showed also in vitro positive effects on hepatocytes [10]. Moreover, it has a strong antibacterial activity against both Gram-negative and Gram-positive pathogens [11] and therefore proves to be a valid aid for gut health maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from its primary function as an energy source for colonocytes, it is a strong mitosis promoter and a differentiation agent for intestinal epithelial cells [8], as it acts as a histone deacetylase (HDAC) inhibitor [9]. It showed also in vitro positive effects on hepatocytes [10]. Moreover, it has a strong antibacterial activity against both Gram-negative and Gram-positive pathogens [11] and therefore proves to be a valid aid for gut health maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…A monolayer hepatocyte-Kupffer cell and a double-layered enterohepatic co-culture have been also established recently by our research group from swine [13,19], but to the best of our knowledge, no similar avian cell cultures were available until now. From chickens, mainly tumorigenic cell lines, such as the Chicken Hepatocellular Carcinoma Cell Line (indicated as LMH cells) [20,21] or embryonic liver cell cultures [22] were used.…”
Section: Discussionmentioning
confidence: 99%
“…The newly prepared chicken cell cultures enable studies concerning the specific role of parenchymal and NP cells as the main liver cell fraction, and the hepatocyte-NP cell co-culture model can mimic various inflammatory states by setting different cell type ratios. The applied ratio of 6:1 (hepatocytes to NP cells) refers to a milder hepatic inflammation with moderate intrahepatic macrophage migration [13]. On this co-culture, the interaction of the inflammatory and stress response can be studied, including molecular alterations of cell function, such as the pro-and anti-inflammatory cytokine production and the redox homeostasis of the cultured liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, conventional in vitro culture systems are known to lack hepatocyte functions; therefore, it is necessary to establish and make available a functional culture system that maintains their specific function. Many studies have demonstrated the maintenance and differentiation of hepatocytes cultured with a variety of non-hepatic cells [21][22][23]. The cell-associated and soluble factors were shown to keep the hepatocytes morphologically and functionally differentiated [24][25][26].…”
Section: Discussionmentioning
confidence: 99%